Carnivorous pitcher plants: Insights in an old topic - Mithöfer, Axel (Phytochemistry (Oxford), 2011)
Nepenthes and other pitcher plants obtain many nutrients from caught insect. The mechanisms that are involved in trapping and retaining prey are presented. Moreover, our knowledge of the pitcher fluid composition, which is responsible for prey digestion and making nutrients available for the plant, is summarized and discussed. [Display omitted] ► Carnivorous Nepenthes plants attract, trap and digest insect prey for additional nutrients. ► The protein composition of the digestion fluid is reported. ► Secondary metabolites have also been described for the fluid. ► Most enzymes are employed in prey digestion but some show antimicrobial activities. Plant insect interactions are usually recognized as a scenario where herbivorous insects feed on a host plant. However, also the opposite situation is known, where plants feed on insects. Carnivorous pitcher plants of the genus Nepenthes as well as other pitcher plants obtain many nutrients from caught insect prey. Special features of the pitcher traps’ surface are responsible for attraction and trapping insects. Once caught, the prey is digested in the fluid of the pitchers to release nutrients and make them available for the plant. Nutrients are taken up by special glands localized on the inner surface of the pitchers. These glands also secrete the hydrolyzing enzymes into the digestion fluid. Although this is known for more than 100 years, our knowledge of the pitcher fluid composition is still limited. Only in recent years some enzymes have been purified from the pitcher fluid and their corresponding genes could be identified. Among them, many pathogenesis-related proteins have been identified, most of which exhibiting hydrolytic activities. The role of these proteins as well as the role of secondary metabolites, which have been identified in the pitcher fluid, is discussed in general and in the context of further studies on carnivorous plants that might give answers to basic questions in plant biology.